Arquitectura Portuguesa face à Globalização - Elza Liliana de Oliveira Carneiro Lopes (2012)
With the passage of the years '70 to '80 twentieth century, and the progressive realization of the emergence of so-called globalization, the world has changed inordinate. The territory, due to the great development of the means of communication and transportation, extended to another dimension, the global. They spread values and, as such, would not be behind the culture, whereas, the architecture has undergone considerable transformations. Thus, concepts such as national borders or place no longer have the previous meaning. Around these years of change are, however, several opposing views. On one hand, some say that these years have meant an end. Others, on the other hand, say that that was the beginning of a promising cycle. And the Portuguese Architecture? What will be done when her entry into the global market? An architecture that sometimes was ahead, and at other times remained short of what was produced in the rest of the World, he now holds a global visibility. An architecture that seeks not only the teachings beyond its borders, but it is also a reference for other countries created their icons, globalized up. Public procurement in the vast majority, are now international, being necessary to give answers that fit with the current situation. The crisis is one of the other realities, many leading architects to emigrate. Most leaves Portugal with intentions to return, but have already evident difficulties that this will entail. Many, however, create their ateliers and begin to build a life abroad. Nevertheless, the European crisis is a reality, which contributes to the market and change orders derive increasingly from emerging countries. Currently there are many debates about changes in our environment and architecture. Debate over an architecture that emerges, and how the new generation born within the new technology responds to this current situation. Times changed, as well as their constraints, and the levels of those requirements have changed. It is necessary to reflect on the reality in which we live when debating about continuity or rupture of Portuguese Architecture.